2013
DOI: 10.1021/ic401057f
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Transverse Anisotropy in CoIII–CoII–CoIII Mixed-Valence Complex toward Slow Magnetic Relaxation

Abstract: Two cobalt mixed-valence complexes with different substituents have been prepared and structurally characterized by single-crystal X-ray diffraction to alter slow magnetic relaxation by tailoring the transverse anisotropy. The trinuclear complexes [(L(1))4Co3(H2O)2](NO3)4·CH3OH·5H2O (1-NO3) and [(L(2))4Co3(H2O)2](NO3)4·6H2O (2-NO3) feature a distorted octahedral Co(II) strongly hindered in a trinuclear Co(III)-Co(II)-Co(III) mixed-valence array. Detailed magnetic studies of 1-NO3 and 2-NO3 have been conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(33 citation statements)
references
References 57 publications
(92 reference statements)
2
31
0
Order By: Relevance
“…1b), whose up and down field-sweeping branches merge as H-0. This behaviour resembles closely that found for some other Co II ions with dominant easy-plane anisotropy [5][6][7][8][9] . Two intriguing questions that need to be addressed are, on the one hand, why do Co II spins with D40 relax so slowly at low T and, on the other, why is this relaxation only visible under finite magnetic fields.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…1b), whose up and down field-sweeping branches merge as H-0. This behaviour resembles closely that found for some other Co II ions with dominant easy-plane anisotropy [5][6][7][8][9] . Two intriguing questions that need to be addressed are, on the one hand, why do Co II spins with D40 relax so slowly at low T and, on the other, why is this relaxation only visible under finite magnetic fields.…”
Section: Resultssupporting
confidence: 87%
“…The same or similar behaviour has thereafter been reported for a number of other Co II complexes [5][6][7][8][9] as well as for lineal Fe II complexes 10 . However, a detailed microscopic interpretation of this phenomenon is still missing.…”
supporting
confidence: 85%
“…Another pseudo-octahedral complex, [Co(abpt) 2 (tcm) 2 ] ( 62 ) (abpt = 4-amino-3,5-bis(2-pyridyl)-1,2,4-triazole and tcm = tricyanomethanide), has also been reported to exhibit easy plane anisotropy, with a spin reversal barrier of U eff = 85.7 K. This is the highest reported barrier thus far for this special sub-class of SIMs 69. A further example of a Co( ii ) system where the authors suggest a similar mechanism is operative is to be found in [(L 2 ) 4 Co 3 (H 2 O) 2 ](NO 3 ) 4 ( 63 ) (where L 2 is the ligand prepared from the Schiff-base condensation of pyridine-2-carboxylate and carbohydrazone) 70. The system features a single Co( ii ) ion in six-coordinate distorted octahedreal geometry, which forms the centre of a trinuclear Co III –Co II –Co III array.…”
Section: Single-ion Magnets With Easy-plane Anisotropymentioning
confidence: 90%
“…The ZFS parameters of D = 20.8 and 29.8 cm -1 , E < 0.1 and < 0.65 cm -1 , and g iso factors = 2.3 and 2.4 were determined for 102 and 103, respectively, based on magnetic studies and EPR data. Their D parameter is of the same order of magnitude, but only complex 103 exhibited slow relaxing magnetization with U eff = 5.5 cm -1 under an applied dc field of 1000 Oe [206].…”
Section: Edited June 25mentioning
confidence: 94%